Efektivitas Penggunaan Aplikasi Sebagai Moderasi Pengaruh Kualitas Pelayanan dan Citra Merek Terhadap Keputusan Pembelian - Diansyah, Diansyah; Saputra, Agung Ryandika (Universitas Batanghari Jambi, 2024)
This study aims to determine the effect of service quality and brand image which is moderated by the effectiveness of using the application on purchasing decisions. The population in this study used a sample of 326 respondents who are Ruangguru application users in Indonesia. The data collection technique used was a non-probability sampling technique with purposive sampling by distributing research questionnaires using Google forms on social media. The data processing method uses smartPLS with the aim of testing the hypothesis. The results of this study indicate that service quality has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions, the effectiveness of using applications has proven to have a positive and significant effect on purchasing decisions, the effectiveness of using applications has proven significant and can moderate on the effect of service quality on purchasing decisions, the effectiveness of using the application is proven to be significant and can moderate the effect of brand image on purchasing decisions. This research recommends Ruangguru to increase purchases, it is suggested to be able to further increase the effectiveness of the application so that customers can easily use the Ruangguru application. This is because some Ruangguru application users have difficulty understanding and using the features in the Ruangguru application. The Ruangguru application is expected to be able to maintain a brand image and service quality that is good enough to maintain or increase purchasing decisions on the Ruangguru application.